2017
DOI: 10.1186/s12894-017-0212-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and treatment for ovotesticular disorder of sex development (OT-DSD) - experience based on a Chinese series

Abstract: BackgroundThe aim of this study is to review and present the clinical features and process of evaluation and treatment for OT-DSD in a single center in recent years in China.MethodsSixteen patients with OT-DSD during the past 4 years underwent the evaluation and treatment in a single center. The clinical characteristics and outcomes of surgery were analyzed.ResultsThe surgical age ranged from 17 months to 66 months with a mean age of 20 months, and the mean follow-up was 30 months (4 months to 56 months). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 18 publications
1
27
2
Order By: Relevance
“…Unilateral and bilateral cryptorchidism were common at 65%. [5][6][7][8][9][10][11]14,15,18 Uterus was found in 79% (11/14) of the cases with male or ambiguous external genitalia (5 and 4). These uteri were bi or unicornuated and always possessed a fallopian tube on at least one side.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unilateral and bilateral cryptorchidism were common at 65%. [5][6][7][8][9][10][11]14,15,18 Uterus was found in 79% (11/14) of the cases with male or ambiguous external genitalia (5 and 4). These uteri were bi or unicornuated and always possessed a fallopian tube on at least one side.…”
Section: Discussionmentioning
confidence: 99%
“…All patients with genital ambiguity had been raised as male with subsequent surgical removal of Mullerian structures and unilateral gonadectomy (►Table 1). [6][7][8][10][11][12][13][14][15] The data suggested that urogenital reconstructive surgery is necessary, therefore a multidisciplinary team approach should be activated as soon as possible, once the diagnosis of 46,XX/47,XXY is made. This can lead to appropriate presurgical intervention for the patients and families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The production of ovarian steroids can also suppress expression of gonadotropins in testicular tissue via a negative feedback effect, resulting in tubular atrophy, poor germ cell development, Leydig cell hyperplasia, and sclerosis that finally causes degeneration of the testicular tissue. 15 As the testosterone production may decline to inadequate levels because of the testicular regression, the consideration of substitutive hormonal treatment should be initiated. 14 An infant born with ambiguous external genitalia presents a major challenge, not only for establishing the diagnosis but also the complexities surrounding any decision about gender assignment.…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis for our patient included ovotesticular disorder of sex development which is defined by the presence of testicular tissue with seminiferous tubules and ovarian tissue with primordial follicles in the same individual 6. However, the absence of ovarian tissue as it was measured by undetectable oestrogen levels after β-hCG stimulation suggests that the abdominal gonad was a streak gonad and therefore the patient could not be classified as having ovotesticular DSD.…”
Section: Differential Diagnosismentioning
confidence: 98%